Bispectrum at NLO in single field inflation: conservation and squeezed limit - Ignatios Antoniadis; Jules Cunat; Auttakit Chatrabhuti; Hiroshi Isono (European Physical Journal C: Particles and Fields)
Abstract In a recent paper, we computed the bispectrum of primordial density perturbations in CMB to second order in the slow-roll parameters of single field inflation, and found logarithmic infrared contributions that diverge in both large physical distances and squeezed limit where one momentum vanishes. In this work, we provide an independent test of the result by checking its conservation and the validity of the consistency relation between the squeezed limit of the bispectrum and the square of the power spectrum. Despite the violation of the main assumption for its general proofs which is the finiteness of the relevant observables in these limits, we find that the identity continues to hold in the vicinity of the squeezed limit and large time.